Improving Students' Creative Thinking in Primary Schools - Harahap, Nuriadani; Sari Ritonga, Delfita (International Journal of Students Education, 2023)
Creative thinking is thinking that creates an idea or produces new ideas in understanding something.Creative thinking is an important ability in the world of education, especially for students. Students can use these skills to solve problems through creative approaches and solutions. This article discusses the importance of developing creative thinking in students, the factors that influence its development, and strategies that facilitate this process in an educational environment. Students' creative thinking methods involve the ability to see situations from different points of view, imagine, innovate, and find unique solutions. Factors such as the learning environment, teacher thinking, and curriculum can influence the development of creative thinking skills. A supportive environment, which fosters tolerance for new ideas and encourages the exploration of innovative ideas, can play an important role in strengthening these abilities. Strategies for improving students' creative thinking include a problem-based learning approach, using techniques such as brainstorming, role-playing, and visualization. Developing space to experiment, exchange ideas and develop collaborative skills is also important to foster creative thinking. Teachers can help students develop innovative thinking skills by focusing on influencing factors and using appropriate strategies to overcome future obstacles. Students' creative thinking skills are the ability to process some information that can produce new ideas in the learning process. This research is classroom action research which consists of two cycles, each of which was carried out in two meetings. Each cycle consists of 4 stages, namely (1) action planning, (2) action implementation, (3) observation and (4) reflection. Data collection in this research was by conducting interviews, observing through observation sheets on students' creative thinking skills, teacher activity sheets in carrying out learning using the project based learning model and documentation.